Effect of Second-Sphere Interactions on the Magnetic Anisotropy of Lanthanide Single-Molecule Magnets: Electrostatic Interactions and Supramolecular Contacts - Aravena-Ponce, D; Aravena-Ponce, D; Llanos-Silva, L; Llanos-Silva, L (American Chemical Society, 2020)
To study how second-sphere interactions affect single-molecule magnet (SMM) properties of mononuclear lanthanide systems, two dysprosium(III) complexes [Dy(N-NCS)3(H2O)5]·0.45(KSCN)(18-crown-6) (1) and [Dy(NO3)2(N-NCS)3(H2O)]·(H2O)(NH4)22(18-crown-6) (2) were synthesized and characterized by single-crystal X-ray diffraction, ac, dc magnetometry, and multireference ab initio calculations. For 1, DyIII complexes are encapsulated between two crown ether molecules, while crown ether molecules and DyIII complexes crystallize in separate rows for 2. Ab initio calculations indicate that encapsulation is detrimental for magnetic anisotropy in the case of 1. This effect is related to a mismatch of the anisotropy axis of the DyIII complex and the symmetry axis of the encapsulating crown ether molecules. Ab initio calculations show that the reorientation of the electrostatic potential exerted by the crown ethers to a more symmetric position produces an enhancement of magnetic anisotropy. We tested the general character of this effect by analyzing a reported DyIII complex encapsulated by crown ether molecules. We also investigated how specific hydrogen-bond interactions affect magnetic anisotropy and show that H-bonds can be beneficial or prejudicial for magnetic anisotropy, depending on their position with respect to the magnetic axis. Our conclusions give general orientations about tuning intermolecular interactions to promote single-molecule magnet properties by controlling electrostatic and supramolecular interactions. Copyright © 2020 American Chemical Society.